POSTOPERATIVE COMPLICATIONS ASSOCIATED WITH MAXILLARY AND MANDIBULAR THIRD MOLAR REMOVAL: A COMPARATIVE CLINICAL ANALYSIS - Irgashev Shokhrukh Khasanovich,; Kholliyev Ulug’bek, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
The more complicated the operation and the worse the condition of the wisdom teeth, the higher the likelihood of postoperative complications. Even the most experienced dentist cannot guarantee their complete absence, since certain negative consequences are practically mandatory and are considered the norm. But there are also specific possible complications that arise due to the patient's fault in the postoperative period or due to the inexperience of the doctor.